2006
DOI: 10.1016/j.jfluchem.2006.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Cesium fluorohydrogenate, Cs(FH)2.3F

Abstract: Cs(FH) 2.3 F is a liquid salt exhibiting a low viscosity of 20.1 cP and a high conductivity of 86.3 mS cm À1 at 25 8C, in spite of the relatively high melting point (16.9 8C). The high density of 2.82 g cm À3 at the liquid state is due to the heavy atomic weight and small size of cesium atom compared to the organic cations of general ionic liquids. The infrared spectroscopy indicates that this salt contains (FH) 2 F À as a main anionic species. The other anionic species such as (FH) 3 F À found in the cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…These results suggest that the coordination numbers of the fluorohydrogenate anion of (CH 3 ) 4 NF· m HF and (C 2 H 5 ) 4 NF· m HF are higher than those of (CH 3 ) 3 N· m HF and (C 2 H 5 ) 3 N· m HF in each m value, respectively. These results are in agreement with the results that a 19 F NMR signal for a stronger Lewis base EMIm(FH) 2.3 F is observed at higher magnetic field than that for a weaker base Cs(FH) 2.3 F . These results will be discussed together with the ionic conductivity and viscosity at the later section.…”
Section: Resultssupporting
confidence: 91%
“…These results suggest that the coordination numbers of the fluorohydrogenate anion of (CH 3 ) 4 NF· m HF and (C 2 H 5 ) 4 NF· m HF are higher than those of (CH 3 ) 3 N· m HF and (C 2 H 5 ) 3 N· m HF in each m value, respectively. These results are in agreement with the results that a 19 F NMR signal for a stronger Lewis base EMIm(FH) 2.3 F is observed at higher magnetic field than that for a weaker base Cs(FH) 2.3 F . These results will be discussed together with the ionic conductivity and viscosity at the later section.…”
Section: Resultssupporting
confidence: 91%
“…[46,47] Results of the MALDI TOF mass spectra ( Figure 1) showed that the CsF supported synthesis method is suitable to achieve PAK without defects. As a consequence of this consideration, the CsF-catalyzed reaction of DFB with secondary aliphatic diamines in the melt has been shown to be successfully for the synthesis of molecularly perfect PAK.…”
Section: Resultsmentioning
confidence: 99%
“…showing high ionic conductivity and low HF dissociation pressure in the CsF-2.3HF molten salt, [12] successive reports on this Cs system cannot be found. This could be attributed to the high cost of CsF that limits the practicality of the CsF-HF system.…”
Section: Introductionmentioning
confidence: 95%